Antitumor evaluation of two selected Pakistani plant extracts on human bone and breast cancer cell lines. Issue 1 (December 2016) - Engel, Nadja; Ali, Iftikhar; Adamus, Anna; Frank, Marcus; Dad, Akber; Ali, Sajjad; Nebe, Barbara; Atif, Muhammad; Ismail, Muhammad; Langer, Peter; Ahmad, Viqar
Abstract Background The medicinal plantsVincetoxicum arnottianum (VSM), Berberis orthobotrys (BORM), Onosma hispida (OHRM and OHAM) andCaccinia macranthera (CMM) are used traditionally in Pakistan and around the world for the treatment of various diseases including cancer, dermal infections, uterine tumor, wounds etc. The present study focuses on the investigation of the selected Pakistani plants for their potential as anticancer agents on human bone and breast cancer cell lines in comparison with non-tumorigenic control cells. Methods The antitumor evaluation was carried out on human bone (MG-63, Saos-2) and breast cancer cell lines (MCF-7, BT-20) in contrast to non-tumorigenic control cells (POB, MCF-12A) via cell viability measurements, cell cycle analysis, Annexin V/PI staining, microscopy based methods as well as migration/invasion determination, metabolic live cell monitoring and western blotting. Results After the first initial screening of the plant extracts, two extracts (BORM, VSM) revealed the highest potential with regard to its antitumor activity. Both extracts caused a significant reduction of cell viability in the breast and bone cancer cells in a concentration dependent manner. The effect of VSM is achieved primarily by inducing a G2/M arrest in the cell cycle and the stabilization of the actin stress fibers leading to reduced cell motility. By contrast BORM's cytotoxic properties were caused through the lysosomal-mediated cell death pathway indicated by an upregulation of Bcl-2 expression. Conclusions The antitumor evaluation of certain medicinal plants presented in this study identified the methanolic root extract ofBerberis orthobotrys and the methanolic extract ofVincetoxicum arnottianum as promising sources for exhibiting the antitumor activity. Therefore, the indigenous use of the herbal remedies for the treatment of cancer and cancer-related diseases has a scientific basis. Moreover, the present study provides a base for phytochemical investigation of the plant extracts.